Examining Depressive Symptoms and Their Predictors in Malaysia: Stress, Locus of Control, and Occupation - Yeoh, Si H.; Tam, Cai L.; Wong, Chee P.; Bonn, Gregory (Frontiers in Psychology, 2017)
The 2015 National Health and Morbidity Survey estimated that over 29% of the adult population of Malaysia suffers from mental distress, a nearly 3-fold increase from the 10.7% estimated by the NHMS in 1996 pointing to the potential beginnings of a public health crisis. This study aimed to better understand this trend by assessing depressive symptoms and their correlates in a cross-section of Malaysians. Specifically, it assesses stress, perceived locus of control, and various socio-demographic variables as possible predictors of depressive symptoms in the Malaysian context. A total of 728 adults from three Malaysian states (Selangor, Penang, Terengganu) completed Beck’s depression inventory as well as several other measures: 10% of respondents reported experiencing severe levels of depressive symptoms, 11% reported moderate and 15% reported mild depressive symptoms indicating that Malaysians are experiencing high levels of emotional distress. When controlling for the influence of other variables, depressive symptoms were predictably related to higher levels of stress and lower levels of internal locus of control. Ethnic Chinese Malaysians, housewives and those engaged in professional-type occupations reported less depressive symptoms. Business owners reported more depressive symptoms. Further research should look more into Malaysians’ subjective experience of stress and depression as well as explore environmental factors that may be contributing to mental health issues. It is argued that future policies can be designed to better balance individual mental health needs with economic growth.